2023
DOI: 10.3390/jpm13030450
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Analysis of Breast Microbiome Highlights the Abundance of Rothia Genus in Tumor Tissues

Abstract: Breast cancer is one of the main global priorities in terms of public health. It remains the most frequent cancer in women and is the leading cause of their death. The human microbiome plays various roles in maintaining health by ensuring a dynamic balance with the host or in the appearance of various pathologies including breast cancer. In this study, we performed an analysis of bacterial signature differences between tumor and adjacent tissues of breast cancer patients in Morocco. Using 16S rRNA gene sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Zhang et al (2028), using liquid chromatography MS-based global metabolomics coupled with targeted metabolomics, demonstrated that the human microbiome can be significantly perturbed by exposure to xenobiotic mixtures, resulting in dysbiosis and metabolite-modified profiles that play an important role in the host’s health [ 66 ]. With regard to BC, it is well-known that human microbiome-related disturbance may contribute to BC development by producing toxins or promoting inflammation, while certain types of bacteria may have positive effects against BC [ 67 ]. Recently, network biology techniques were used to identify xenobiotics that target hub proteins in the human interactomes, mainly in disease-associated proteins and contaminant-sensitive biomarkers [ 68 ], suggesting a new omics field, environmental interactomics.…”
Section: Advances and Trends In Omics Fields Related To Bc Exposomicsmentioning
confidence: 99%
“…Zhang et al (2028), using liquid chromatography MS-based global metabolomics coupled with targeted metabolomics, demonstrated that the human microbiome can be significantly perturbed by exposure to xenobiotic mixtures, resulting in dysbiosis and metabolite-modified profiles that play an important role in the host’s health [ 66 ]. With regard to BC, it is well-known that human microbiome-related disturbance may contribute to BC development by producing toxins or promoting inflammation, while certain types of bacteria may have positive effects against BC [ 67 ]. Recently, network biology techniques were used to identify xenobiotics that target hub proteins in the human interactomes, mainly in disease-associated proteins and contaminant-sensitive biomarkers [ 68 ], suggesting a new omics field, environmental interactomics.…”
Section: Advances and Trends In Omics Fields Related To Bc Exposomicsmentioning
confidence: 99%
“…Thus, a methylomics-based study used a methylatyed DNA immunoprecipitation microarray (MeDIP-chip) on DNA samples isolated from the white blood cells of young patients with BC, emphasizing the hypermethylation of several genes, such as APC , HDAC1 , GSK1 , SLC6A3 , Rab40C , ZNF584 , and FOXD3 [ 142 ]. Additionally, metagenomics analyses of normal and malignant breast microbiomes using 16S rRNA gene sequencing identified specific microbial communities that could serve as potential biomarkers for prognoses and diagnoses, with implications in developing novel strategies for the treatment of BC patients [ 145 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…Breast cancer is believed to be a complicated disease that arises from a combination of environmental, microbiome, and genetics factors that increase its pathogenicity. 3 Indeed, at the genetics level, BC is associated with a number of genes with high- and moderate to low-penetrance susceptibility, implicated in DNA damage response. Breast cancer type 1 susceptibility protein (BRCA1) located on chromosome 17 and breast cancer type 2 susceptibility protein ( BRCA2 ) located on chromosome 13 are the most important genes associated with BC, with a 60% and 55%, respectively, cumulative risks.…”
Section: Introductionmentioning
confidence: 99%